Efeito dos treinamentos funcional e concorrente na funcionalidade, inflammaging e fenótipos de linfócitos T de memória de idosas - Vasconcelos, Alan Bruno Silva (2021)
Because of advances in society, life expectancy has increased and, thus, the number of elderly people tends to grow in the coming decades. However, during aging, the elderly may find it difficult to do their daily activities, such as dressing or sitting and getting up from a chair, for example. In addition, these people may have more diseases, because the defense system, known as the immune system, loses part of its ability to protect the human body. In the body of elderly people, there is also an inflammation that contributes to these consequences throughout aging. In this context, physical exercise can favor a healthier, active aging and with an increase in the elderly's autonomy. However, there are still doubts about what is the best type of exercise for elderly people thinking about improving the defense system. Thus, this thesis investigated the effects of functional training and concurrent training (strength training + running) on performance in activities similar to daily life, on inflammation and immune system cells of elderly women. Two studies were carried out with elderly women separated into groups to carry out functional training, concurrent training and a group that did not exercise. The elderly women participated in exercise sessions held three times a week, for six months (first study) and four months (second study). The functional training group performed exercises similar to daily activities, such as sitting and standing, carrying, pulling and pushing. The competing training group practiced weight training at a gym and at the end they also did a run at the end. The elderly women were monitored during the months and underwent tests to assess their ability to perform movements as quickly as possible (muscle power) and tasks similar to those of everyday life. Blood was also collected to watch for inflammation and immune cells. The results found showed that both functional training and concurrent training improved the ability to perform daily activities, quickly, because it increased the power of the muscles. It was also seen that the training reduced body fat and for the protection of the organism, while increasing the number of other cells that present a better profile for the defense of the human body. Therefore, both forms of exercise can be used to promote health among elderly women.